EXPRESSION OF RECOMBINANT HUMAN ERYTHROPOIETIN WITH GLYCOSYLATION MODIFICATION IN HEK293T CELLS - Endah Puji Septisetyani; Yana Rubiyana; Popi Hadi Wisnuwardhani; Andri Wardiana; Adi Santoso (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Stability of erythropoietin (EPO) depends on its glycosylation states. With more glycosylation sites, the EPO protein will be more stable and also increase its half-life. A construct of recombinant human erythropoietin (rhEPO) which contains 2 additional N-link for glycosylation were designed. Based on translation analysis using ORF (open reading frame)-finder and protein alignment analysis using blast-p of NCBI home page, expected recombinant hEPO with additional 6-histidin tag in carboxyl terminus was expressed. HEK293T cells were transfected with recombinant plasmid containing rhEPO by using calcium phosphate method. Expression of rhEPO was detected by dot blot and Western blot analysis using hEPO antibody as the primary antibody and antirabbit antibody with alkaline phospatase linked as the secondary antibody. The bands were detected by BCIP/NBT color development substrate. The data indicated detection of EPO in culture medium of transfected HEK293T cells.Key words: HEK293T cell, calcium phosphate transfection, N-linked glycosylation, recombinant human erythropoietin